Adaptation and evaluation of psychometric properties of HELAM using the Rasch model in the Indonesian context - Trikinasih Handayani; Moh Irma Sukarelawan; Mohd Effendi Ewan Mohd Matore; Much Fuad Saifuddin (International Journal of Evaluation and Research in Education (IJERE), 2023)
Many schools have shifted their learning mode from face to face to fully online in order to reduce virus transmission and avoid learning loss, resulting in accelerated use of the learning management system (LMS). The implementation of online learning over the last 3 years in Indonesia needs to be evaluated. However, the available evaluation scales are in different cultural contexts. Therefore, the existing scales should be adapted. This study aims to adapt and report the psychometric properties of the Hexagonal E-Learning Assessment Model (HELAM) scale in the context of Indonesian culture. The adaptation followed the procedure suggested by Beaton. To achieve a measurement accuracy of up to 0.5 logit at a 99% confidence level, 326 teachers taking the Teacher Professional Education (TPE) program in position program were involved. The psychometric properties of the HELAM scale were analyzed using the Rasch model to improve accuracy and observe the quality of the HELAM scale. The results of the analysis show that the HELAM scale has good psychometric properties in the context of Indonesian culture at the instrument and item level. The elements of reliability and validity have met the good criteria. Thus, the adapted HELAM scale can be applied to the Indonesian context.